KEPUASAN MASYARAKAT ATAS KEBIJAKAN REKLAMASI PANTAI DI WILAYAH MALALAYANG KOTA MANADO - THEREISYE GRACE SALU; JOHNNY POSUMAH; VERY LONDA (Sam Ratulangi University, 2022)
The purpose of this study was to find out how the community's satisfaction with the beach reclamation policyin the Malalayang area, Manado City. This study uses descriptive qualitative research methods. Communitysatisfaction with the coastal reclamation policy can be seen through the relationship between the results in thefield and what the community previously hoped for. There are 3 indicators to measure community satisfaction,namely perceived quality, perceived value, and service user expectations. Based on the results of the study thatcommunity satisfaction with the beach reclamation policy in the Malalayang area of Manado City for theperceived quality it can be said to be quite good, but the government no longer pays attention to the shoulderreclamation area which has resulted in some being neglected and uncontrolled. Meanwhile, the perceivedvalue of this beach reclamation policy has not been fulfilled properly because the impact of losses that thecommunity feels is more and greater than the benefits of this beach reclamation. And the last is the expectationof service users to improve, control and provide assistance to coastal communities.Keywords : Community Satisfaction, Public Policy, Coastal Reclamation